Malaria circumsporozoite protein binds to heparan sulfate proteoglycans associated with the surface membrane of hepatocytes (The Rockefeller University Press, 1993)
During feeding by infected mosquitoes, malaria sporozoites are injected into the host's bloodstream and enter hepatocytes within minutes. The remarkable target cell specificity of this parasite may be explained by the presence of receptors for the region II-plus of the circumsporozoite protein (CS) on the basolateral domain of the plasma membrane of hepatocytes. We have now identified these receptors as heparan sulfate proteoglycans (HSPG). The binding of CS to the receptors is abolished by heparitinase treatment, indicating that the recognition of region II-plus is via the glycosaminoglycan chains. We have purified and partially characterized the CS-binding HSPGs from HepG2 cells. They have a molecular weight of 400,000-700,000, are tightly associated with the plasma membrane, and are released from the cell surface by very mild trypsinization, a property which the CS receptors share with the syndecan family of proteoglycans.